2011
DOI: 10.1111/j.1460-9592.2011.03626.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of timing and temperature of oral fluids ingested after minor surgery in preschool children on vomiting: a prospective, randomized, clinical study

Abstract: A first oral intake in children 1 h after anesthesia for minor surgery seems not to increase the incidence of vomiting as long as the ingested fluid is at body temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Prospective observational study 74/107 (69%) children undergoing nonelective procedural sedation had solid contents or calculated fluid volume > 1.2 ml kg À1 Gagey et al 92 34 infants undergoing pyloromyotomy Prospective observational study Ultrasound monitoring useful to appropriately guide the choice of the anaesthetic induction technique. It allowed a nonrapid sequence induction technique to be used in 30/34 (88%) infants with an empty stomach opioid, 107 an equal or lower incidence of vomiting [105][106][107][108][109][110][111][112] and a shorter postanaesthesia care unit or hospital stay (Table 25). 107,108,110 On the contrary, the postoperative vomiting incidence was found to be increased when children were forced to drink.…”
Section: Gastric Ultrasoundmentioning
confidence: 99%
“…Prospective observational study 74/107 (69%) children undergoing nonelective procedural sedation had solid contents or calculated fluid volume > 1.2 ml kg À1 Gagey et al 92 34 infants undergoing pyloromyotomy Prospective observational study Ultrasound monitoring useful to appropriately guide the choice of the anaesthetic induction technique. It allowed a nonrapid sequence induction technique to be used in 30/34 (88%) infants with an empty stomach opioid, 107 an equal or lower incidence of vomiting [105][106][107][108][109][110][111][112] and a shorter postanaesthesia care unit or hospital stay (Table 25). 107,108,110 On the contrary, the postoperative vomiting incidence was found to be increased when children were forced to drink.…”
Section: Gastric Ultrasoundmentioning
confidence: 99%
“…In another study with children undergoing inguinal hernia or orchiopexy undescended testis surgeries under general anesthesia, some patients received clear fluids after 2 hours, and some received them 1 hour after emergence. These authors found that oral intake 1 hour after emergence did not increase the incidence of vomiting [8]. In our study, we also investigated the safety of oral intake 1-2 hours after emergence, as well as just after emergence based on their own needs.…”
Section: Discussionmentioning
confidence: 88%
“…We obtained written informed consent from the patients' parents. Following consent, and assuming a statistical power of 90% and an alpha of 5% [8], 180 children undergoing elective magnetic resonance imaging (MRI) (ASA status I/II, aged 1 month to 13 years) were randomly assigned to one of three groups. Patients were excluded if they were in an ASA III/IV status, had any barbiturate allergies, porphyria, a condition which could delay gastric emptying time, gastrointestinal disorders, or underwent an MRI with general anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While earlier studies advocated against early oral intake following surgery, due to the increased risk of nausea and vomiting, later studies have shown that mandatory postoperative fasting does not reduce the incidence of PONV . It has further been shown that the children who received oral fluids on demand were less bothered by pain and happier than those who were expected to fast postoperatively …”
Section: Discussionmentioning
confidence: 99%